Efficiency of natural and artificial reproduction of Baltic salmon as the result of peculiarities in its freshwater life period - Mitans, A.R. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva, 1975)
The population structure and dynamics, the distribution, behaviour, feeding, growth, smoltification and descent of salmon (Salmo salar) fry in the Latvian rivers including parrs and smolts, are described. The ecological peculiarities of the freshwater period of life are studied, and main factors determining the formation of recruits and the year-class fecundity are revealed. The population model is constructed, the indices of mortality, return rate and other quantitative characteristics of natural reproduction are calculated. Theoretical prerequisites and practical recommendations on raising the efficiency of artificial reproduction by means of introducing modified biological standards and optimal terms of smolt output are given. Published Not Known